Liquid Posterior Fossa Epidural Hematoma in Pediatric Trauma: A Single-Center Case Series - Han, Kun; Li, Zhaojian; Yin, Hongwei; Yao, Weicheng; Lan, Xiaolei; Bo, Yongli (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2018)
Background Liquid posterior fossa epidural hematoma (LPFEH) following head trauma is uncommon, and very few such cases have been described in the literature. Eight patients with this entity and their treatments are presented here.Methods We performed a single-institution retrospective analysis of all patients with diagnosed LPFEH over a 3-year period. Collected data included clinical history, laboratory results, treatment, and review of all imaging studies performed.Results Eight pediatric cases were identified with imaging findings consistent with LPFEH; no adult case was identified. Enlargement of ventricles appeared on computed tomography (CT) in six cases, and secondary epilepsy onset occurred in three cases with severe dilated ventricles. Routine hematologic and coagulation tests failed to disclose anemia or abnormal coagulation in each case. Five patients underwent burr-hole drainage of the hematoma and recovered completely. Conservative therapy was adopted in three patients for small hematomas, and hematoma enlargement was not observed in the follow-up CT scans.Conclusions LPFEH is a rare subtype of traumatic epidural hematoma specifically recognized in the pediatric population. Minimally invasive burr-hole drainage is a feasible procedure for the patient with evident space-occupying effect. Coagulation dysfunction or low hemoglobin as a possible contributing factor and its role in formation of LPFEH was excluded.
Keywords: computed tomography; pediatric; epidural hematoma; liquid; posterior fossa